East Asia and Cosmopolitan Memory - SAITO, Hiro (Institutional Knowledge at Singapore Management University, 2014)
This paper examines institutional underpinnings of the so-called “history problem” in East Asia, a set of controversies over how Japan should commemorate the Asia-Pacific War. I first illustrate how the history problem resulted from a collision of mutually reinforcing nationalist memories in Japan, China, and South Korea. Next, I introduce two intersecting dialectics that hold the key to explaining the trajectory and dynamics of the history problem. One is a dialectic of nationalism and cosmopolitanism as two logics of constructing collective memory, and another is a dialectic of commemoration and historiography as two modes of appropriating the past. I then argue that the recent trajectory and dynamics of the history problem points to the emergence of cosmopolitan memory, coupled with historians’ critique of nationalist memory. In conclusion, I critically assess future prospects of cosmopolitan memory and reconciliation in East Asia.